International order and economic integration - Röpke, Wilhelm (Dordrecht, D. Reidel Pub. Co., 1959)
The book's principal aim is to draw attention to the essential problems of international order and the fundamentals involved and also as a guide through the maze of questions in the field of international economic relations.
Translation of Internationale Ordnung.
rpm 14/11/2017
Loans
Keywords: Economic integration; Economic cooperation; Economic policy; Economics